VIOLENCE AGAINST WOMEN IN DELHI (ANALYZING THE NATURE, TIME, PLACE, AGE AND RELATIONSHIP BETWEEN A RAPE VICTIM AND OFFENDER) - Chaudhary, Tara Shanker (European Scientific Journal, ESJ, 2015)
Today global warming and climate change, natural hazards and disasters, environmental pollution and degradation, hunger and poverty, terrorism and wars etc are the biggest concern for the global community. I just want to add one more problem which is prevalent across all the societies irrespective of the level of their economic development- crime. I would like to call it a social disaster. It’s a disaster which disrupts the functioning of the society. In recent years, news papers are full of brutal rape cases which show an alarming rise of rape in metros like Delhi. Currently Delhi is reporting 4 rape cases every day. Rape is a crime which questions over public security as well as public health. The present study is a content analysis of rape cases published in daily news. The aim of the study is to find out the place of crime, site of the crime, nature of the crime, age of the victim and offender and the relationship between victim and offender. A total of 298 rape cases were found in last three years of reporting. It was found that most of the victims were unmarried and below 18 years of age. In majority of the cases victim knew the perpetrator. 25 percent cases of rape were in form of gang rape which shows the brutality of the crime. More than 60 percent rape victims were found below 18 years of age and 75% rapists were known to the victim. 10% cases of rape were found as incest rape. Average age of victims is 17.5 years while average age of the rapists is found 31 years.